2020
DOI: 10.1515/humor-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents creating cartoons: A developmental study of humor

Abstract: Developmental studies on humor have historically approached a limited age range – from birth until early adolescence – and have mostly considered humor interpretation and the production of situational and verbal humor. Focusing on cartooning, a highly demanding cognitive and communication activity, in this paper we aim to provide empirical data drawn from a larger age span than usual – 10 to 18 years old – to better understand what adolescents find humorous and how they create humor. Our corpus comes from nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The following two profiles present a humorous incongruity and vary according to the author's motivation (Pedrazzini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The following two profiles present a humorous incongruity and vary according to the author's motivation (Pedrazzini et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, our results are in line with the literature that reveals a major concern for socio-political issues and civic engagement among adolescents (Flanagan, 2004). In the particular case of cartooning, it has been found that 13-15 years old tend to privilege the creation of committed cartoons in order to condemn from their own viewpoint, faults and vices of society (Pedrazzini et al, 2021). This occurs in a greater proportion than in 10-12 years old.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations